2013
DOI: 10.1302/0301-620x.95b3.30113
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of severe slipped capital femoral epiphysis via the Ganz surgical dislocation and anatomical reduction

Abstract: We present our experience of the modified Dunn procedure in combination with a Ganz surgical dislocation of the hip to treat patients with severe slipped capital femoral epiphysis (SCFE). The aim was to prospectively investigate whether this technique is safe and reproducible. We assessed the degree of reduction, functional outcome, rate of complications, radiological changes and range of movement in the hip. There were 28 patients with a mean follow-up of 38.6 months (24 to 84). The lateral slip angle was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 39 publications
2
52
2
4
Order By: Relevance
“…It is unclear, however, whether revascularization was related to the integrity of the retinacular vessels or if it may have happened through a transphyseal mechanism. Contrary to previous studies [9,18,30], we found three patients with an ICP waveform before dissection and after fixation who later developed osteonecrosis. These represent examples of a false-negative test result.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is unclear, however, whether revascularization was related to the integrity of the retinacular vessels or if it may have happened through a transphyseal mechanism. Contrary to previous studies [9,18,30], we found three patients with an ICP waveform before dissection and after fixation who later developed osteonecrosis. These represent examples of a false-negative test result.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a descriptive analysis of the raw measurements of accuracy showed that ICP monitoring before dissection demonstrated good sensitivity, whereas bleeding after definitive fixation was a highly (100%) specific test. The absence of femoral head perfusion after fixation was also found to have high specificity by Madan et al [18] who reported osteonecrosis in four our of 17 patients with unstable SCFE who had no bleeding before dislocation and after reduction. Similarly, Sankar et al [24] found no perfusion after fixation in three of 27 unstable SCFEs.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Surgical dislocation has been promoted to treat severe SUFE with a low FHO [33][34][35][36][37] however pooled data from 5 studies (SD) [13,15,[28][29][30] showed a high rate of FHO (25%). This rate was comparable to closed reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of treatments options were reported for the study population including epiphysiodesis [10,11], pinning in situ (PIS) [1,7,[12][13][14][15][16][17][18][19], closed reduction and pinning (CRIF) [4,5,11,15,16,18,[20][21][22][23][24][25], open reduction and physeal osteotomy (PO) [1,7,15,26] open reduction and internal fixation (ORIF) [23][24][25]27] and surgical dislocation (SD) [13,15,[28][29][30].…”
Section: Description Of Studiesmentioning
confidence: 99%